2017
DOI: 10.1002/jbt.22010
|View full text |Cite
|
Sign up to set email alerts
|

The toxicological effects of some avermectins on goat liver carbonic anhydrase enzyme

Abstract: Avermectins are used worldwide as antiparasitic drugs in the field of veterinary medicine and as agricultural pesticides and insecticides. Carbonic anhydrase (CA, E.C. 4.2.1.1) is a zinccontaining metalloenzyme that catalyzes the reversible hydration of carbon dioxide (CO 2 ) to yield protons (H + ) and bicarbonate (HCO 3 − ). In this study, some avermectins, including abamectin, doramectin, eprinomectin, and moxidectin, were investigated for in vitro inhibitory effects on the CA enzyme purified from goat live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 73 publications
1
31
0
Order By: Relevance
“…[5][6][7] CAs are extensively found in all kingdoms of life and are classified in seven groups: -, -, -, -, -, -, and -CAs. [13][14][15][16][17] Enzyme ⋯ Zn 2+ − OH − + CO 2 Then ∼Zn 2+ -OHis formed from water coordinated to the Zn 2+ , which exists at the bottom of the active site cavity of CA. [8][9][10][11][12] Out of 16 CA isoenzymes, 12 isoenzymes are catalytically active and differ in their distribution in tissues and organs, subcellular localization, kinetic properties, expression levels, and inhibitor binding dependence.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] CAs are extensively found in all kingdoms of life and are classified in seven groups: -, -, -, -, -, -, and -CAs. [13][14][15][16][17] Enzyme ⋯ Zn 2+ − OH − + CO 2 Then ∼Zn 2+ -OHis formed from water coordinated to the Zn 2+ , which exists at the bottom of the active site cavity of CA. [8][9][10][11][12] Out of 16 CA isoenzymes, 12 isoenzymes are catalytically active and differ in their distribution in tissues and organs, subcellular localization, kinetic properties, expression levels, and inhibitor binding dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Voriconazole is an antifungal medication used to treat a number of fungal infections, and its inhibitory effects against some metabolic enzymes are shown in Table and Figures . Previous research has clearly indicated that the inhibitory effect of Voriconazole against hCA I, hCA II, AChE, and α‐glycosidase is greater than or equal to that of morphine, antioxidant phenols, hydroquinone, taxifolin, spirobisnaphthalenes, caffeic acid phenethyl ester, rosmarinic acid, some hydroperoxides, alcohols and acetates, some ureas, eugenol derivatives, lignans, thioureas, flavonoids, synephrine and phenylephrine, avermectins, antibiotics, and TAC derivatives . The present study adds to this previous literature (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…In 3–7 years after diagnosis of this disease, AD leads to death. At subcellular and cellular levels, AD happens as overproduction of β‐amyloid (Aβ) peptides, further extracellular organization of plaques, synaptic degeneration, intracellular agglomeration of hyperphosphorylated τ protein forming neurofibrillary tangles and neuronal cell death . The death of neurons forcefully reduces the amounts of ACh in cholinergic brain synapses.…”
Section: Discussionmentioning
confidence: 99%